Appearances are deceptive…. (21st May 2013) - Franzen, Daniel; Butsch, Raphael; Chaloupka, Karla
Abstract : A 31-year-old man was referred with sudden onset of a painful periorbital angio-oedema. Assuming a first episode of allergic or acquired angio-oedema, the patient was treated with a plasma-derived C1 esterase inhibitor, tranexamic acid and fresh-frozen plasma, after the initial treatment with corticosteroids and histamine blockers was unsuccessful. As blood cultures grew group A streptococci, the diagnosis of periorbital necrotising fasciitis was made, and treatment was subsequently changed to clindamycin and ceftriaxone. Necrotising fasciitis involving the periorbita is a rare and potentially lethal differential diagnosis of acute angio-oedema, in particular if accompanied by severe pain and/or fever. Knowledge on the appearance of this disorder cannot be overemphasised, as only early recognition and immediate initiation of high-dose penicillin and clindamycin combined with tissue debridement help to decrease the mortality and morbidity.